Xanthomonas arboricola pv. pruni, causal agent of bacterial spot of stone fruits and almond: its genomic and phenotypic characteristics in the X. arboricola species context. (18th April 2018) - Garita‐Cambronero, Jerson; Palacio‐Bielsa, Ana; Cubero, Jaime
Summary: Background: Xanthomonas arboricola pv. pruni ( Xap ) causes bacterial spot of stone fruits and almond, an important disease that may reduce the yield and vigour of the trees, as well as the marketability of affected fruits. Xap lies within the Xanthomonas genus, which has been intensively studied because of its strain specialization and host range complexity. Here, we summarize the recent advances in our understanding of the complexities of Xap, including studies of the molecular features that result after comparative phenotypic and genomic analyses, in order to obtain a clearer overview of the bacterial behaviour and infection mechanism in the context of the X. arboricola species. Taxonomic status: Bacteria; Phylum Proteobacteria ; Class Gammaproteobacteria ; Order Xanthomonadales ; Family Xanthomonadaceae ; Genus Xanthomonas ; Species X. arboricola ; Pathovar pruni . Host range and symptoms: Xap infects most Prunus species, including apricot, peach, nectarine, plum and almond, and occasionally cherry. Symptoms are found on leaves, fruits, twigs and branches or trunks. In severe infections, defoliation and fruit dropping may occur. Distribution: Bacterial spot of stone fruits and almond is worldwide in distribution, with Xap being isolated in Africa, North and South America, Asia, Europe and Oceania. It is a common disease in geographical areas in which stone fruits and almonds are grown. Xap is listed as a quarantine organism in several areas of the world. Genome: The genomes of six isolates from Xap have been publicly released. The genome consists of a single chromosome of around 5 000 000 bp with 65 mol% GC content and an extrachromosomal plasmid element of around 41 000 bp with 62 mol% GC content. Genomic comparative studies in X. arboricola have allowed the identification of putative virulence components associated with the infection process of bacterial spot of stone fruits and almond. Disease control: Management of bacterial spot of stone fruits and almond is based on an integrated approach that comprises essential measures to avoid Xap introduction in a production zone, as well as the use of tolerant or resistant plant material and chemical treatments, mainly based on copper compounds. Management programmes also include the use of appropriate cultivation practices when the disease is already established. Finally, for the effective control of the disease, appropriate detection and characterization methods are needed for use in symptomatic or asymptomatic samples as a first approach for pathogen exclusion. Useful websites: https://gd.eppo.int/taxon/XANTPR ;http://www.cost.eu/COST_Actions/ca/CA16107 ;http://www.xanthomonas.org